Regulatory approaches to evaluation of biosimilars for treatment of rheumatic diseases - D. V. Goryachev; M. Yu. Telnykh; N. D. Bunyatyan (Регуляторные исследования и экспертиза лекарственных средств, 2018)
The article discusses the design of development programmes for biosimilars used to treat patients with rheumatic diseases. It analyses the most popular definitions of biosimilars that are used in Russia and abroad, as well as regulatory approaches to establishing biosimilarity. The authors describe the design of confirmatory clinical trials and draw attention to the fact that equivalence margins need to be justified on both clinical and statistical grounds. The article substantiates the need to continuously improve the requirements for and approaches to the assessment of the programmes’ applicability to biosimilars evaluation.